A modern approach for the sensing of aqueous Al(III) ion by Ni(II) Salen‐type Schiff base complexes. (30th June 2019) - Mohan, Nithya; S. S., Sreejith; Begum, P.M. Sabura; Kurup, M.R. Prathapachandra
Abstract : In this work, we explore a modern concept of transmetalation (metal exchange) for the effective recognition of aqueous Al(III) ion. Three different Ni(II) salen‐type Schiff base complexes with different spacer diimine groups were prepared for the metal exchange reaction. These probes recognize Al(III) both colorimetically as well as fluorimetrically. The efficiency in sensing is mainly due to the low emission characteristics of the respective Ni(II) complexes which results in enhanced emission on the formation of Al(III) complex. The geometry of the central Ni(II) metal ion in the probe plays a pivotal role in the sensing action with the highest sensitivity being shown by the Ni(II) metal center with distorted square pyramidal geometry. Further DFT calculations and the energetics involved in the sensing mechanism via the formation of Al(III) complexes substantiates the experimental results. Abstract : Detection of Al(III) ion by their respective Ni(II) metal complexes via transmetalation are probed using various experimental and theoretical methods. The three Ni(II) complexes are prepared by varying the diimino spacer group and the detection efficiency is a function of the geometry of the metal center present in the probe.